2017
DOI: 10.1097/igc.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2, Randomized, Open-Label Study of Irosustat Versus Megestrol Acetate in Advanced Endometrial Cancer

Abstract: Objective: Advanced/metastatic or recurrent endometrial cancer has a poor prognosis. Malignant endometrial tissue has high steroid sulphatase (STS) activity. The aim of this study was to evaluate STS as a therapeutic target in patients with endometrial cancer. Methods: This was a phase 2, multicenter, international, open-label, randomized (1:1), 2-arm study of the STS inhibitor oral irosustat 40 mg/d versus oral megestrol acetate 160 mg/d in women with advanced/metastatic or recurrent estrogen receptorYpositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…STS inhibitors have been considered as novel anticancer agents where phase II clinical study has already been performed in ER-positive advanced/recurrent EC, however with no convincing results for STS inhibitor irosustat vs. progestin megestrol acetate (Pautier et al, 2017) with the progression free survival of 16 and 32 weeks, respectively. STS inhibitor thus performed worse as compared to the current medical treatment for recurrent EC.…”
Section: Discussionmentioning
confidence: 99%
“…STS inhibitors have been considered as novel anticancer agents where phase II clinical study has already been performed in ER-positive advanced/recurrent EC, however with no convincing results for STS inhibitor irosustat vs. progestin megestrol acetate (Pautier et al, 2017) with the progression free survival of 16 and 32 weeks, respectively. STS inhibitor thus performed worse as compared to the current medical treatment for recurrent EC.…”
Section: Discussionmentioning
confidence: 99%
“…Accessed on date: February 2018) and a phase II trial started 2016 ( http://adisinsight.springer.com/drugs/800041929 ) . ∧ NSCLC: non-small cell lung cancer ∧∧ LAM: lymphangioleiomyomatosis 1 Perez Carrion et al ( 1994 ), 2 Arnold and Einspanier ( 2013 ), 3 Delvoux et al ( 2014 ), 4 Konings et al ( 2017 ), 5 Järvensivu et al ( 2018 ), 6 Husen et al ( 2006 ), 7 Saloniemi et al ( 2010 ), 8 Gargano et al ( 2015 ), 9 Soubhye et al ( 2015 ) 10 Day et al ( 2013 ), 11 Wang et al ( 2017 ), 12 BroŽic et al ( 2011 ), 13 Kikuchi et al ( 2014 ), 14 Purohit and Foster ( 2012 ), 15 Pautier et al ( 2017 ), 16 Palmieri et al ( 2017a ), 17 Palmieri et al ( 2017b ), 18 Pohl et al ( 2014 ), 19 Ma et al ( 2004 ), 20 Rose et al ( 2000 ), 21 Lindemann et al ( 2014 ), 22 Slomovitz et al ( 2015 ), 23 NCT00932152; 25 Lu et al ( 2017 ) . …”
Section: Drug Developmentmentioning
confidence: 99%
“…More recently, there is a re-emerging interest in developing novel intracrine drugs. A number of compounds are in their clinical phases, like STS inhibitors (Maltais and Poirier, 2011 ; Woo et al, 2011 ; Purohit and Foster, 2012 ; Pohl et al, 2014 ; Pautier et al, 2017 ) or inhibitors of AKR1C3/17βHSD5, which are of particular interest because this enzyme has crucial role in androgen/estrogen and prostaglandin biosynthesis (Penning, 2017 ). Bayer's AKR1C3/17βHSD5 inhibitor BAY 1128688 has a modified estrogen core, it interferes with both pathways, and is in phase II clinical trial for endometriosis (Bothe et al, 2017 ).…”
Section: Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a phase 3 trial comparing zoptarelin to doxorubicin also failed to improve the overall survival (OS) of patients with advanced endometrial cancer [6]. Several other clinical trials of both targeted therapies and chemotherapeutic regimens have also demonstrated disappointing outcomes in advanced and recurrent endometrial carcinoma, underscoring the challenging nature of this disease [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%